Targeting ER α-glucosidase I with a single-dose iminosugar treatment protects against lethal influenza and dengue virus infections - Warfield, K; Alonzi, DS; Hill, JC; Caputo, AT; Roversi, P; Kiappes, JL; Sheets, N; Duchars, M; Dwek, RA; Biggins, J; Barnard, D; Shresta, S; et al. (American Chemical Society, 2020)
Influenza and dengue viruses present a growing global threat to public health. Both viruses depend on the host endoplasmic reticulum (ER) glycoprotein folding pathway. In 2014, Sadat et al. reported two siblings with a rare genetic defect in ER alpha-glucosidase I (ER Glu I) who showed resistance to viral infections, identifying ER Glu I as a key antiviral target. Here we show that a single dose of UV-4B (the hydrochloride salt form of N-(9′-methoxynonyl)-1- deoxynojirimycin; MON-DNJ) capable of inhibiting Glu I in vivo is sufficient to prevent death in mice infected with lethal viral doses, even when treatment is started as late as 48 hours post-infection. The first crystal structure of mammalian ER Glu I will constitute the basis for the development of potent and selective inhibitors. Targeting ER Glu I with UV-4B derived compounds may alter treatment paradigms for acute viral disease through development of a single-dose therapeutic regime.